Construção de câmara de luz ultravioleta para fotopolimerização de fases estacionárias monolíticas - Vaz, Fernando Antonio Simas; Oliveira, Marcone Augusto Leal de; Queiroz, Marco Polo Garcia de; Ribeiro, Sidney José Lima [UNESP] (Sociedade Brasileira de Química, 2008)
The assembly of a photochemical reactor with six fluorescent lamps, used for photopolymerizations is described. This chamber presents a mobile support, allowing the placement of samples at different heights and a safety lock that interrupts the radiation, if it is opened during operation. The mirrored internal walls avoid the dispersion and non-uniform distribution of light. There is no high heating because the own character of the used lamps. All parts could be purchased in commerce with less than U$ 150,00. This reactor was successfully used for monolithic stationary phase photopolymerization.
Coinstruction of ultraviolet-light chamber for monolithic stationary phases photo-polymerization
Keywords: photochemical reactor; photopolymerization; ultraviolet crosslinker